McArdle's Disease Presenting as Unexplained Dyspnea in a Young Woman - Nha Voduc; Katherine A Webb; Christine D'Arsigny; Ian McBride; Denis E O'Donnell (Canadian Respiratory Journal)
McArdle's disease is a rare, inherited deficiency of myophosphorylase, an enzyme required for the utilization of glycogen. Patients with myophosphorylase deficiency classically present with exercise intolerance, leg pain and muscle fatigue. The case of a young woman with exertional dyspnea and leg cramps is described. Exercise testing confirmed the presence of exercise intolerance and demonstrated an accelerated heart rate response, despite the absence of an anaerobic threshold and a respiratory exchange ratio of less than 1.0. Subsequent ischemic forearm testing and muscle biopsy confirmed the diagnosis of myophosphorylase deficiency. Evaluation of lung mechanics with esophageal pressure measurements demonstrated the presence of respiratory muscle weakness and early fatiguability, suggesting that the patient's dyspnea might have been attributable to an increased respiratory effort. Dyspnea is not a classic symptom associated with myophosphorylase deficiency, although subclinical respiratory muscle impairment may be present. No previous studies have evaluated respiratory muscle function during exercise in patients with myophosphorylase deficiency.